Effect of glyphosate and P on the growth and nutrition of Coffea arabica cultivars and on weed control - Yanna Karoline Santos da Costa (Nature Portfolio, 2021)
Abstract The effect of the phosphorus (P) and glyphosate interactions on the growth and nutrition of Arabica coffee cultivars (Coffea arabica), as well as on the control of Ipomoea grandifolia and Urochloa decumbens, was evaluated. Catuaí-Amarelo/IAC-62 and Catuaí-Vermelho/IAC-144 cultivars did not show glyphosate poisoning, regardless of the soil P content. However, glyphosate reduced the growth of Catuaí-Vermelho/IAC-144. In addition, the soil P content influenced the height, leaf area and dry matter of Catuaí-Amarelo/IAC-62, and the absorption of P and Ca in both cultivars. On the other hand, glyphosate efficiently controlled U. decumbens but not I. grandifolia. Glyphosate effectiveness on I. grandifolia decreased as the soil P content increased. In addition, the soil P content and the glyphosate influenced the P content in I. grandifolia and U. decumbens plants. The soil P content influenced the growth and absorption of other nutrients by coffee plants as well as glyphosate effectiveness on weed control.